Numerical Simulation Procedure for Modeling TGO Crack Propagation and TGO Growth in Thermal Barrier Coatings upon Thermal-Mechanical Cycling - Ding Jun; Huang Xia; Chen Song; Yang E-Chuan (Advances in Materials Science and Engineering)
This paper reports a numerical simulation procedure to model crack propagation in TGO layer and TGO growth near a surface groove in metal substrate upon multiple thermal-mechanical cycles. The material property change method is employed to model TGO formation cycle by cycle, and the creep properties for constituent materials are also incorporated. Two columns of repeated nodes are placed along the interface of the potential crack, and these nodes are bonded together as one node at a geometrical location. In terms of critical crack opening displacement criterion, onset of crack propagation in TGO layer has been determined by finite element analyses in comparison with that without predefined crack. Then, according to the results from the previous analyses, the input values for the critical failure parameters for the subsequent analyses can be decided. The robust capabilities of restart analysis in ABAQUS help to implement the overall simulation for TGO crack propagation. The comparison of the TGO final deformation profile between numerical and experimental observation shows a good agreement indicating the correctness and effectiveness of the present procedure, which can guide the prediction of the failure in TGO for the future design and optimization for TBC system.